2016
DOI: 10.1155/2016/2056416
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenesis from Dental Pulp Derived Stem Cells: A Novel Conditioned Medium Including Melatonin within a Mixture of Hyaluronic, Butyric, and Retinoic Acids

Abstract: Human dental pulp stem cells (hDPSCs) have shown relevant potential for cell therapy in the orthopedic and odontoiatric fields. The optimization of their osteogenic potential is currently a major challenge. Vascular endothelial growth factor A (VEGF A) has been recently reported to act as a major conductor of osteogenesis in vitro and in vivo. Here, we attempted to prime endogenous VEGF A expression without the need for viral vector mediated gene transfer technologies. We show that hDPSCs exposure to a mixture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 24 publications
0
30
0
Order By: Relevance
“…The osteogenic differentiation medium must contain: β-glycerophosphate, dexamethasone, ascorbic acid-2-phosphate and combinations of transforming growth factor-beta (TGF-β), bone morphogenetic proteins and vitamin D3 [ 1 , 40 ]. Recently, melatonin or a mixture of hyaluronic, butyric, and retinoic acids have been reported to efficiently promote an osteogenic patterning in human dental pulp stem cells by inducing the transcription of a gene program of osteogenesis [ 41 , 42 ]. The differentiation of ASCs into osteocytes is controlled by various transcription factors as such as Runt-related transcription factor 2 (Runx2), osterix, and β-catenin.…”
Section: Asc Differentiation Potentialmentioning
confidence: 99%
“…The osteogenic differentiation medium must contain: β-glycerophosphate, dexamethasone, ascorbic acid-2-phosphate and combinations of transforming growth factor-beta (TGF-β), bone morphogenetic proteins and vitamin D3 [ 1 , 40 ]. Recently, melatonin or a mixture of hyaluronic, butyric, and retinoic acids have been reported to efficiently promote an osteogenic patterning in human dental pulp stem cells by inducing the transcription of a gene program of osteogenesis [ 41 , 42 ]. The differentiation of ASCs into osteocytes is controlled by various transcription factors as such as Runt-related transcription factor 2 (Runx2), osterix, and β-catenin.…”
Section: Asc Differentiation Potentialmentioning
confidence: 99%
“…Melatonin functions as a broad-spectrum antioxidant [ 10 , 11 , 12 ] and has anti-apoptotic and anti-autophagic effects [ 13 , 14 , 15 , 16 , 17 ]. Moreover, melatonin modulates osteogenic and adipogenic differentiation, in different kinds of mesenchymal stem cells, including dental pulp-derived stem cells and adipose-derived stem cells [ 18 , 19 ]. Recently, Kim and Yoo [ 20 ] reported that a combination of FSS and melatonin activates anabolic proteins through the p-ERK in MC3T3-E1 osteoblast cells.…”
Section: Introductionmentioning
confidence: 99%
“…ROS have been recognized as toxic and harmful by-products for stem cells, resulting in DNA damage, premature senescence or cell death [22]. MSCs are largely known for their ability to restore tissue function and differentiate into several phenotypes under appropriate stimuli [23], including osteogenic, chondrogenic, cardiogenic and adipogenic lineages [24][25][26][27]. Nevertheless, as previously demonstrated by Liao N et al, hADSCs expanded for different passages, showing high mRNA levels of p16, p21 and p53 and an increased ROS production, associated with the appearance of a senescent phenotype.…”
Section: Discussionmentioning
confidence: 99%